La théorie du culte de l’offensive et la formulation des choix stratégiques - David, Charles-Philippe (Études internationales, 1989)
The theory of the Cult of the Offensive clearly stands out among the most recent works being conducted in Strategic Studies. The aim of this article is to better understand this new theoretical contribution by looking at its strengths and weaknesses, and by applying it to the case of the evolving American naval strategy. The central elements of this approach will be analysed in order to explain the significant growth that the American Navy has experienced since the start of the 1980s. In this manner, it will be possible to perceive as much the applicability of this theory as the relevance of the case study, to show the value of strategic studies as a field which seeks a greater understanding of strategic choices.